2010
DOI: 10.1117/12.838809
|View full text |Cite
|
Sign up to set email alerts
|

Subjective assessment of HDTV content: comparison of quality across HDTV formats

Abstract: This paper reports on a series of experiments designed to examine the subjective quality of HDTV encoded video at a distance of 4H from a 46 inch widescreen LCD TV. A common set of video sequences varying in spatial and temporal complexity were encoded at different H.264 encoding profiles. Each video source used in the tests was available in 720p at 50 fps (720p/50) and in 1080i at 25 fps (1080i/25) HDTV formats. Each clip was then encoded in CBR mode using H.264 at bit rates ranging from 1 up to 20Mbit/s with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Several publications discuss the influence of transmission distortions on the quality of experience in the 2D case [3,4,5]. In the 3D case, a transmission distortion in one view or in both views is perceived differently.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications discuss the influence of transmission distortions on the quality of experience in the 2D case [3,4,5]. In the 3D case, a transmission distortion in one view or in both views is perceived differently.…”
Section: Introductionmentioning
confidence: 99%
“…6 and Loncaric et.al. 7 showed that for the same bitrates, 720p50 delivers a better perceived quality compared to 1080i50.…”
Section: Related Workmentioning
confidence: 99%
“…Subjective analysis [1] showed that same packet loss can have significantly different impact on a user's perceived quality for 3D than 2D video. The relationship between bit rate and perceptual quality of HDTV contents was investigated in [4] and illustrated that users are more affected and annoyed by long and widely spread packet losses than bursts occurred for transmission errors. This paper proposes an efficient error concealment strategy and appropriate subjective testing scenario for transmitted 3D Videos.…”
Section: Introductionmentioning
confidence: 99%